The stepsisters - Mallery, Susan (Toronto : Mira, an imprint of Harlequin books, 2021)
Once upon a time, when her dad married Sage's mom, Daisy was thrilled to get a bright and shiny new sister. But Sage was beautiful and popular, everything Daisy was not, and she made sure Daisy knew it. Sage didn't have Daisy's smarts, so she used her popularity as a weapon, putting Daisy down to elevate herself. After the divorce, the stepsisters' rivalry continued until the final, improbable straw: Daisy married Sage's first love, and Sage fled California. Eighteen years, two kids and one troubled marriage later, Daisy never expects - or wants - to see Sage again. But when the little sister they have in common needs them both, they put aside their differences to care for Cassidy.
Keywords: Families -- Fiction; Stepsisters -- Fiction; Friendship -- Fiction; Divorce -- Fiction; Life change events -- Fiction; Domestic fiction